ChemInform Abstract: Thiosemicarbazone Copper Complexes as Competent Catalysts for Olefin Cyclopropanations. Issue 3 (22nd January 2013) - Youssef, Nabil S.; El‐Seidy, Ahmed M. A.; Schiavoni, Marco; Castano, Brunilde; Ragaini, Fabio; Gallo, Emma; Caselli, Alessandro
Abstract Several copper complexes of thiosemicarbazones are prepared and tested as catalysts in the cyclopropanation reaction of α‐methylstyrene (Ia).